PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS PERHUBUNGAN KOTA BIMA - Mulyadin; Mawar Hidayanti; Fitra Safira Danilla (Publika Citra Media, 2024)
This study aims to determine the Influence of Leadership and Work Motivation on Employee Job Satisfaction at the Bima City Transportation Office. The approach used in the study is an associative approach. The population in the study was 188 people with a sample of 32 ASN people. Data collection techniques used were observation, questionnaires, and literature studies. The data analysis technique used was multiple linear regression analysis processed using the Statistical Product and Service Solution (SPSS) version 20 program. The results of the study showed that leadership and work motivation simultaneously had a significant effect on Employee Job Satisfaction at the Bima City Transportation Office.